Horadam Spinors - Tülay Erişir (Journal of Mathematics)
Spinors can be expressed as Lie algebra of infinitesimal rotations. Spinors are also defined as elements of a vector space which carries a linear representation of the Clifford algebra typically. The motivation for this study is to define a new and particular sequence. An essential feature of this sequence is that while a generalization is being made, spinors, which have a lot of use in physics, are used. This new sequence defined using spinor representations is called the Horadam spinor sequence; formulas such as the Binet formula, generating function formula, and Cassini formula are given. The Horadam spinors given in this study are a generalization of the spinor representations of Horadam quaternion sequences.